Somatosensory Evoked Potentials Study in Cervical Spondylotic Myelopathy Patients - Kareem, Ruaa M.; Al-madfai, Zaid; A. Al-Sheikhly, Abdulmuttaleb (Journal of the Faculty of Medicine Baghdad, 2014)
Background: Cervical spondylotic myelopathy (CSM) is considered the most serious consequence of cervical spondylosis and accounts for the majority of non_traumatic paraparesis and/or quadriparesis. The electrical property of the spinal cord and its susceptibility to injuries renders electrophysiology relevant to the management of CSM. Somatosensory evoked potentials study (SEPs) is an objective assessment of the functional integrity of the neural pathway.Objective: Utilizing both of the median and the posterior tibial SEPs in evaluating the functional integrity of the cervical spinal cord in patients with CSM and to correlate the SEPs findings with the clinical and MRI findings.Patients and methods: Twenty two patients with CSM (11 male and 11 female) ranging in age from 29 to 77 years with a mean age of (56 ±11) years and matched with 25 healthy subjects of the control group were enrolled in this study.Results: In this study, 86.36% of patients had abnormal SEPs study (either tibial or median or both tests abnormal), with 68.2% abnormal tibial and 63.6% abnormal median. There was no difference between right and left side study of neither median nor tibial SEPs studies (P>0.05). Loss of N13, loss or delayed N20 and loss or delayed N13-N20 were the most frequent abnormalities for median SEPs and loss or delayed P37 and LP-P37 were most frequent abnormalities in tibial SEPs. Results showed that normal SEPs findings mostly correlated with mild and early myelopathy (grade-1 and grade-2 Nurick). Abnormal SEPs findings are useful in prediction the progression of myelopathy in patients with mild clinical neurological deficits in the early stages of the disease.Conclusion: This study concluded that both median and tibial SEPs montages are useful important objective assessment of the spinal cord function to evaluate patients with CSM since MRI and SEPs may evaluate different aspects of the disease process.